Development of a continuous manufacturing process for self-reinforced composites using multi-step highly drawn polypropylene tapes. (16th March 2020) - Kim, Dong Woo; Kim, Yoon Sang; Jung, Yong Chae; Kim, Seong Yun; Song, Jong Man; Kim, Minkook; Kim, Jaewoo
Abstract: Despite the benefits of recycling, impact resistance, and lightweightness, polypropylene (PP) self-reinforced composites (SRCs) still suffer from a lack of research, especially in continuous manufacturing processes. Herein we report a comprehensive study, from the four-step high-ratio drawing of PP-tapes to the continuous manufacturing of SRCs. The mechanical properties of the PP-tape depend strongly on the final draw ratio with the intermediate drawing history having a negligible effect. Mechanical improvements accompany increases in melting temperature and crystallinity, and a decrease in density. PP-SRC was manufactured by continuous double-belt pressing, with optimum performance attained when processed with a 87-148-80 (°C) temperature profile. Structural integrity was not attained at lower temperatures due to poor impregnation, whereas higher temperatures degraded the mechanical properties of the PP-SRC by relaxing the highly drawn PP-tapes. Finally, an analytical approach based on micro-computed tomography, PP-tape relaxation, and rule-of-mixture calculations led to accurate predictions of experimental moduli. Graphical abstract: Image 1 Highlights: Highly drawn polypropylene (PP) tape is prepared using a four-step drawing system. The effects of draw ratio and history on the properties of the PP tape are examined. PP self-reinforced composites (PP-SRCs) are formed by continuous double-belt pressing. Improper processing temperatures cause poor impregnation or tape relaxation. An analytic approach leads to accurate predictions of experimental moduli.